2019
DOI: 10.15835/nbha47411614
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Some Plant Growth Regulators on Natural and Dark-Induced Senescence in Wheat Leaf Segments

Abstract: Senescence is an important developmental process in the life span of a plant. It is affected by several endogenous and exogenous factors such as hormones, darkness, and drought. Hormones are major endogenous factors that affect senescence intensively. In this study, our aim was to investigate the effects of different plant growth regulators; benzyl adenin (BA), spermine (Spm) and spermidine (Spd) on both natural and dark-induced senescence and on γ-aminobutyric acid (GABA) content in wheat leaf segments. Follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Polyamines are involved in key developmental and physiological metabolic processes such as plant cell growth, stress resistance, senescence, and maturation 9 , 10 . Multiple studies have shown that exogenous application of polyamines or an increased content of endogenous polyamine can delay aging 11 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyamines are involved in key developmental and physiological metabolic processes such as plant cell growth, stress resistance, senescence, and maturation 9 , 10 . Multiple studies have shown that exogenous application of polyamines or an increased content of endogenous polyamine can delay aging 11 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Polyamines are involved in key developmental and physiological metabolic processes such as plant cell growth, stress resistance, senescence, and maturation 9,10 . Multiple studies have shown that exogenous application of polyamines or an increased content of endogenous polyamine can delay aging [11][12][13][14] .As a simple and inexpensive technology, shading can prevent summer leaf scorching, allowing plants to perform photosynthesis and delaying plant aging 15 . Zhao et al 16 found that shading alleviated heat damage in…”
mentioning
confidence: 99%